Kecerdasan emosi dan komitmen kerja dalam kalangan guru sekolah menengah di daerah Johor Bahru - Ab. Razak, Nurzawani (2014)
n The purpose of this study is to determine the relationship between the teacher’s emotional intelligence and teacher’s work commitment. The survey is based on the feedback from 180 respondents as sample from three selective schools. Descriptive statistical analysis is done with the application Goleman Emotional Intelligence (1995) and Allen and Mayer work commitment (1998). The instrument is closed- questionnaire and data was processed using SPSS. Pearson Correlation Test is adopted to observe the significant relationship between the variables. The result indicates that the level of teacher’s emotional intelligence is high. Meanwhile the level of effective commitment, normative commitment and continuous commitment is average. Other than that, the teacher’s emotional intelligence has significant relationship with teacher’s work commitment in secondary schools area Johor Bahru